Digital Financial Innovation, Bank Efficiency, and Sustainability: A Prisma Based Systematic Literature Review in the Banking Sector (2015–2025) - Diaz, Marsela (Journal Research of Social Science, Economics, and Management, 2025)
This study presents a Systematic Literature Review (SLR) that integrates three main pillars digital financial innovation, banking efficiency, and sustainability using the PRISMA approach and the CIMO framework for the period 2015–2025. The digitalization of financial services and the adoption of fintech have become key drivers of the transformation of the global banking industry, impacting operational efficiency, profitability, risk management, and the sustainability agenda. Through a rigorous identification and selection process of 30 primary studies (60 reports) from Scopus and other relevant sources, this study maps the geographic context, forms of digital intervention, mechanisms of influence, and resulting outputs. The results show that research is dominated by studies based on the Asian context, particularly China, with a focus on digital transformation, fintech adoption, and regulatory sandbox implementation. The main mechanisms identified include data-driven decision-making, digital governance, network effects, automation, and financial inclusion mechanisms. Meanwhile, the dominant outputs are cost efficiency, profitability, risk stability, and improved ESG performance, although research related to the circular economy and social implications is still limited. The main contribution of this SLR is the development of a CIMO-based mapping and the development of a Tri-Dimensional Digital Banking Framework conceptual framework that connects digital technology, regulatory governance, and sustainability. These findings provide practical implications for banks, regulators, and policymakers regarding digital transformation strategies, risk governance, and ESG integration. Furthermore, this study opens a broader research agenda related to geographic equity, enriching methodologies, and expanding outputs toward efficient, inclusive, and sustainable digital financial innovation.